SAVITZKY-GOLAY METHOD FOR THE EVALUATION OF DECELERATION OF THE FIRCTION LIFT - Paweł Lonkwic (Advances in Science and Technology Research Journal, 2017)
Due to self-acting variability of operating conditions during the work of lifting devices, it is fundamental for the gears to stop the cabin at any clearance height. The operating conditions are changed by dust contamination influencing a proper braking process of the gear. This article presents the independent tests results. The impact of progressive gear geometry on the braking distance both in variable operating conditions and variable loading is analyzed. The tests were conducted for the gear applied in short distance transportation devices. Changing operating conditions were obtained by using various lubricating agents. The following five types of the gears were used for the tests: ASG100, PP16, PR2000, KB160. CHP 2000 gear was tested as a new solution. The tests were conducted using a free fall method. The test results obtained from an experiment were approximated by using Savitzky-Golay method.